Ticks and tick‐borne bacterial pathogens found on hard ticks (Acari: Ixodidae) on cattle in the Central River region of The Gambia - Kargbo, Alpha; Osman, Aamir M.; Jawo, Edrisa; Fatty, Lamin K. M.; Collere, Flavia C. M.; André, Marcos R. [UNESP]; Hassan‐Kadle, Ahmed A.; Vieira, Thállitha S. W. J.; Machado, Rosangela Z. [UNESP]; Vieira, Rafael F. C. (Wiley, 2025)
Ticks are significant vectors of pathogens affecting both animals and humans, with the climate and environment of Sub-Saharan Africa providing ideal conditions for their growth. However, there are limited data on ticks and tick-borne pathogens (T&TBPs) in cattle in The Gambia. This study aimed to identify tick species on cattle and conduct molecular screening for T&TBPs. A total of 92 ticks were collected from 306 indigenous cattle. Ticks were first identified morphologically using taxonomic keys and then confirmed molecularly through DNA sequencing. DNA was extracted from the right fourth leg of six representative ticks for species confirmation, while 77 whole adult ticks were used for screening T&TBPs. Screening polymerase chain reaction (PCR) assays targeted Anaplasma marginale msp1β gene, Ehrlichia spp. dsb gene and hemotropic Mycoplasma spp. 16S rRNA gene. Ehrlichia-positive samples underwent additional assays targeting the sodB, 16S rRNA and groEL genes, followed by Sanger sequencing and phylogenetic analyses. A total of 92 (53 M, 37 F and two nymphs) ticks were collected from 30/306 (9.8%; 95% confidence interval [CI]: 5.6%-12.2%) cattle. Adult ticks were identified as Hyalomma marginatum (73/92; 79.3%; 45 M and 28 F), Amblyomma variegatum (8/92; 8.7%; 8 M), Hyalomma rufipes (4/92; 4.3%; 4 F) and Rhipicephalus evertsi (1/92; 1.1%; one F). The 16S rRNA sequences of six (four engorged female and two nymphs) ticks showed 98.6-100% identity with reference sequences from Rhipicephalus geigyi. Twelve out of 77 (15.6%) ticks tested positive for at least one TBP. Eight H. marginatum (six M and two F) (10.4%) were positive for Ehrlichia spp. dsb gene, three H. marginatum (two M and one F) (3.9%) for A. marginale and two (one H. marginatum F and one A. variegatum M) (2.6%) for hemotropic Mycoplasma spp. All Ehrlichia-positive samples showed 100% detection for the 16S rRNA gene and 62.5% for the sodB gene. BLASTn analysis revealed 99.3%-99.7% identity with Ehrlichia sp. from Brazil and 98.2%-99.3% identity with E. minasensis from Panama and Pakistan. Phylogenetic analysis grouped the sequences from this study with Ehrlichia spp. and E. minasensis from ticks in the Czech Republic and Brazil. This study identified various tick species and pathogens in cattle from The Gambia, including the first report of E. minasensis, A. marginale and hemotropic Mycoplasma spp. in the country. These findings highlight the importance of ongoing surveillance and research on tick-borne diseases in the region.